Development of duplex TaqMan PCR assays for detection and quantification of Trypanosoma cruzi infection in wild and domestic reservoirs - Wehrendt, Diana Patricia (2018)
A major question of epidemiological relevance in Chagas disease studies is to understand the dynamics ofT.cruzi infection in sylvatic and domestic transmission cycles and to trace the origins of (re)emerging casesin areas under vector or disease surveillance. Conventional parasitological methods lack sensitivity and molecularapproaches, such as the polymerase chain reaction may ll in this gap, provided that a standardizedmethod can be developed and validated.We have developed two duplex Real Time PCR assays for sensitive detection of T.cruzi satellite or minicirclerepetitive sequences in blood samples from mammal reservoirs, incorporating an internal amplicationstandard that allows distinction of false negative PCR ndings due to inadequate conditions of storageand transport of samples, DNA degradation during nucleic acid purication and/or inhibition of PCR byinterfering substances present in the sample. The housekeeping gene that encodes the interphotoreceptorretinoid-binding protein (IRBP) has been selected as internal standard, because it is highly conserved amongall mammal species and its usefulness as a DNA integrity control was previously reported in a conventionalPCR protocol. Based on the alignment of the IRBP sequence available for several domestic and wild reservoirspecies, we designed primers and a TaqMan probe to a highly conserved region. The analytical sensitivitywas 0.01 par. eq/mL and 0.1 par.eq/mL for satDNA/IRBP duplex and kDNA/IRBP duplex, respectively, astested with two series of canine blood spiked with known concentrations of Silvio X10 (Tc I) and CL-Brener(Tc VI) cultured epimastigotes. The assays were evaluated in DNA extracts from blood samples of 87 wildand 147 domestic animals. Our DNA integrity control worked well for wild reservoir species including smallrodents (Akodon toba, Galea leucoblephara, Rattus rattus), opossums (Didelphis virginiana, D. marsupialis),bats (Tadarida brasiliensis, Promops nasutus, Desmodus rotundus) and other mammals such as the skunk,viscacha, wildcat, brown brocket deer, hare and Pampas fox. Mean Ct values for IRBP amplication variedamong species between 24 and 33. For domestic reservoirs, IRBP amplied in dog, cat, cow, sheep, goat,horse and mule specimens with mean Ct values between 23 and 25. In T.cruzi infected cases the assaysallowed quantication of parasitic loads.Our results promote the use of these methods for rapid and accurate screening of T.cruzi infection in dierentspecies of reservoirs.